Fear of Missing Out and e-WOM as Drivers of Impulsive Buying: Evidence from Muslim Gen Z's Purchase Intentions on TikTok in Support of the SDGs - Adinda Nur Fitria; Afifah Nur Millatina; Sri Cahyaning Umi Salama (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study examines the influence of Fear of Missing Out (FOMO) and Electronic Word of Mouth (e-WOM) on Impulsive Buying behavior among Generation Z, with Purchase Intention serving as a mediating variable. It also evaluates the implications of these relationships for sustainable consumption in support of SDG 12 and SDG 8. Theoretical framework: The research is grounded in consumer behavior theory, stimulus–organism–response (S–O–R) theory, and social influence theory, which explain how emotional and informational stimuli shape purchase intentions and impulsive buying decisions in digital commerce. Literature review: Previous studies have established that FOMO and e-WOM significantly influence online purchasing behavior. However, empirical findings remain inconsistent regarding their direct effects on impulsive buying, while the mediating role of Purchase Intention has received limited attention, particularly among Muslim Generation Z consumers in social commerce environments. Methods: A quantitative research design was employed using an online survey involving 212 respondents selected through accidental sampling. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS to evaluate both direct and indirect relationships among the proposed constructs. Results: The findings indicate that FOMO significantly influences both Purchase Intention and Impulsive Buying. In contrast, e-WOM has a positive and significant effect on Purchase Intention but does not directly affect Impulsive Buying. Purchase Intention positively influences Impulsive Buying and partially mediates the relationships between FOMO, e-WOM, and Impulsive Buying, although the mediation effect is relatively weak. Implications: The findings provide practical insights for e-commerce platforms, digital marketers, and policymakers to develop responsible marketing strategies that reduce emotionally driven purchasing behavior while supporting sustainable consumption and economic development aligned with SDG 12 and SDG 8. Novelty: This study contributes by integrating FOMO, e-WOM, Purchase Intention, and Impulsive Buying into a single SEM-PLS model while highlighting the mediating role of Purchase Intention among Muslim Generation Z consumers within the context of digital commerce and sustainable development.